Attempted Endoscopic Closure of a Pancreaticocolonic Fistula with an Over-The-Scope Clip - Gray II, Darrell M; Mullady, Daniel K (JOP. Journal of the Pancreas, 2012)
Context Spontaneous development of fistulae is an uncommon complication of acute pancreatitis. Until recently, surgical management has been the standard of care. Endoscopic treatment has been described with hemoclips and glue. Case report We report a case of a gentleman with a history of recurrent episodes of acute pancreatitis who presented with symptoms correlating with the development of a pancreatic-colonic fistula. Closure of the fistula was attempted with an over-the-scope clip. Conclusion More evidence is needed to determine criteria for use of over-the-scope clip in closure of GI and pancreatic fistulae. Image: Endoscopic view of the angled guidewire protruding through the fistula and the over-the-scope clip.